Menopause-associated depression: impact of oxidative stress and neuroinflammation on the central nervous system—a review - Liang, Gengfan; Kow, Audrey Siew Foong; Yusof, Rohana; Tham, Chau Ling; Ho, Yu-Cheng; Lee, Ming Tatt (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Perimenopausal depression, occurring shortly before or after menopause, is characterized by symptoms such as emotional depression, anxiety, and stress, often accompanied by endocrine dysfunction, particularly hypogonadism and senescence. Current treatments for perimenopausal depression primarily provide symptomatic relief but often come with undesirable side effects. The development of agents targeting the specific pathologies of perimenopausal depression has been relatively slow. The erratic fluctuations in estrogen and progesterone levels during the perimenopausal stage expose women to the risk of developing perimenopausal-associated depression. These hormonal changes trigger the production of proinflammatory mediators and induce oxidative stress, leading to progressive neuronal damage. This review serves as a comprehensive overview of the underlying mechanisms contributing to perimenopausal depression. It aims to shed light on the complex relationship between perimenopausal hormones, neurotransmitters, brain-derived neurotrophic factors, chronic inflammation, oxidative stress, and perimenopausal depression. By summarizing the intricate interplay between hormonal fluctuations, neurotransmitter activity, brain-derived neurotrophic factors, chronic inflammation, oxidative stress, and perimenopausal depression, this review aims to stimulate further research in this field. The hope is that an increased understanding of these mechanisms will pave the way for the development of more effective therapeutic targets, ultimately reducing the risk of depression during the menopausal stage for the betterment of psychological wellbeing.